Effect of gas–liquid surface disturbance during cryogenic liquid pressurization with helium. (December 2022) - Baek, Seungwhan; Yu, Isang; Park, Kwangkun; Jung, Youngsuk; Cho, Kiejoo
Highlights: Cryogenic propellant is pressurized with hot helium in typical launch vehicle. Depressurization of ullage was observed with cold helium input to the LN2 tank. Cryogenic liquid droplet propagation observed during the pressurization. The ullage temperature and pressure decreased due to the ullage cooling effect. The ullage depressurization is possible during the helium gas with liquid droplets. Abstract: In liquid propellant propulsion systems, helium pressurization is required to transfer liquid propellant from the tank to the engine. When a cryogenic liquid propellant is used, the tank becomes pressurized by relatively high temperature helium. Typically, the ullage pressure increases with the helium inflow. However, in one particular case, the ullage pressure reduced while cold helium was supplied through direct gas injection. High-velocity gaseous helium strikes the cryogenic liquid surface that generates the liquid splash in the ullage. The cryogenic liquid splash in the ullage then transfers heat between the gas and the liquid. Therefore, the ullage pressure decreases because of the decrease in the ullage temperature. The pressure behavior of the cryogenic tank during the gas inflow is experimentally examined, and the depressurization during the pressurization process is analyzed. The results indicate that the gas–liquid interface disturbance decreases the ullage pressure. The observed gas–liquid interface disturbance effect can be employed in pressure decrease applications in cryogenic liquid storage tanks.